2005
DOI: 10.1007/s10856-005-4753-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrothermal treatment with CaCl2 solution on surface property and cell response of titanium implants

Abstract: In order to obtain early and good osteointegration after implantation of a titanium implant in the human body, the surface modified treatments using NaOH or H(2)O(2) etc. were reported. In this study, titanium was hydrothermally treated with CaCl(2) solutions at 200 degrees C for 24hr (CaCl(2)-HT). Scanning electron microscope (SEM) observation clearly showed apatite deposition on the surface of CaCl(2) HT treated titanium faster than other chemical treated titanium immersion in simulated body fluid. X-ray pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
0
53
2
Order By: Relevance
“…Non-process (NP) group specimens received no treatment. In the negative control (DW) group, specimens were hydrothermally treated in distilled water at 200°C for 24 h. In the calcium (Ca) and magnesium (Mg) groups, plates were treated at 200°C for 24 h with a 10 mmol/L solution of CaCl 2 or MgCl 2 , respectively, as reported previously [15,18]. After the treatment, surface Ra was ranged 0.20-0.22 lm; subsequently, all specimens were washed with DW and stored under a vacuum to prevent surface contamination.…”
Section: Titanium Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-process (NP) group specimens received no treatment. In the negative control (DW) group, specimens were hydrothermally treated in distilled water at 200°C for 24 h. In the calcium (Ca) and magnesium (Mg) groups, plates were treated at 200°C for 24 h with a 10 mmol/L solution of CaCl 2 or MgCl 2 , respectively, as reported previously [15,18]. After the treatment, surface Ra was ranged 0.20-0.22 lm; subsequently, all specimens were washed with DW and stored under a vacuum to prevent surface contamination.…”
Section: Titanium Platesmentioning
confidence: 99%
“…In addition, a laser micro-grooved surface was effective for connective tissue attachment, and this attachment effectively resisted peri-implant bone resorption [8]. In the present study, we use hydrothermal modification of titanium with divalent calcium or magnesium cations [14,15], which are known to be indispensable for cell-to-substratum contact [16,17]. We hypothesized that this technique may promote the adhesion of epithelial cells or fibroblasts to titanium.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the surface charge of the materials should be negative for the Ca 2+ to bond on its surface [13][14][15][16] . Our previous studies demonstrated that Ca-modified Ti can be made based on hydrothermal treatment of Ti with CaCl2 solution 17,19) . However, the results may be taken as the enhancement of bonding of Ca 2+ to negatively charged Ti surface under hydrothermal condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported that Ti can be modified with Ca using hydrothermal treatment and ozone treatment [17][18][19] . The Ca-modified Ti showed enhanced initial cell attachment and differentiation, when osteoblastic cells were incubated on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, researchers have actively performed many studies on the applications of sodium titanate thin films in implants Nishiguchi et al, 1999;Jonášová et al, 2003;Muramatsu et al, 2003;Wang et al, 2007;Wang et al, 2008). Similar studies have also been performed on calcium titanate thin films (Hanawa et al, 1997;Hamada et al, 2002;Nakagawa et al, 2005;Kon et al, 2007;Ohtsu et al, 2008), titanium dioxide thin films (Ohtsuki et al, 1997;Wang et al, 2001;Wang et al, 2003;Byon et al, 2007), and a nanohydroxyapatite thin film (Xiong et al, 2010), and the excellent biocompatibilities of these films have been reported. Therefore, titanium compound thin films show tremendous promise for use as implant materials.…”
Section: Introductionmentioning
confidence: 88%